Gunung putri: fanatism in the middle of modernity - Utami, I. Inesia Sri; Nasution, S Ali; Maufur, M.; Efendi, I.; Gunadi, G. (International Journal of Psychosocial Rehabilitation, 2020)
Modernization is included in various aspects of life and becomes the driver of transformation in people's lives. The Gunung Putri community, with its gemeinschaft characteristics, upholds religious teachings which then form their own identities. The influx of modernization has divided society into two camps, groups that tend to accept and reject modernization. The purpose of this research is to try to present an analysis of this phenomenon amid the onslaught of modernization that entered the lives of the Gunung Putri community. This research uses a qualitative approach with a case study method. Data collection techniques used are in-depth interviews and observation. The interviewees were selected based on the principle of purposive and snowball techniques. The results of the study found that modernization has led to social changes both in groups that reject and accept modernization. The social conflict that arises because of differences in interpreting theoretical modernization is a natural thing to happen in the dynamics of rural life. Contradictions in the community did not stop social and cultural changes in the life of the Gunung Putri community. This research is limited to the area coverage only on the study of phenomena that occur in the Gunung Putri community. Future studies are expected to be able to examine the phenomenon of modernization in people's lives with a wider range in the territory of Indonesia.